Sir Robin Cooke - McLay, Geoff (Victoria University of Wellington Law Review, 2006)
This article is a tribute to Sir Robin Cooke after his death in 2006. Even though Sir Robin was an international figure of great renown, the author notes that the death of Sir Robin was felt more personal throughout Victoria University of Wellington’s Faculty of Law. The article outlines Sir Robin’s expertise and deep concern for the tradition of the common law, his admirable work ethic, and his passion for cricket.